Culture, self, and cognition: adding Africa to the mix - Janse van Rensburg, Gerard (Department of Psychology, 2017)
Cross-cultural differences in cognition have been well established across the world, and differences in Individualism (IND) and Collectivism (COL) are believed to underlie the majority of these cultural variations. IND-COL measures are frequently used to categorise nations as either IND or COL and these nations are subsequently used to draw IND or COL samples for comparison on various cognitive tasks. The multicultural nature of South Africa and inconsistent findings on IND-COL in SA makes such IND-COL categorisation problematic. African nations have also been conspicuously missing from international cross-cultural research on culture and cognition. This study set out to explore the utility of IND-COL measures in South Africa, with special regard to possible racial or linguistic differences. It also set out to remedy the absence of African nations in the international literature by replicating a previous study on culture and cognition within a South African sample. The shortened HVIC scale by Triandis and Gelfand (1998) was used to explore racial and linguistic differences in terms of IND-COL within a South African university population (N = 1380). Psychometric analyses showed good reliability, internal consistency, and construct validity. Regression analysis revealed race and language as poor predictors of IND. COL prediction was marginally better, accounting for 8.2% of variance, and with African Language as a significant predictor (beta = -.432, p < .01). To address the absence of Africa in the literature, replication of the eye-tracking and memory study by Chua et al. (2005) was attempted in a South African university population (N = 52). Due to the multicultural nature of South Africa, participants were recruited and sorted according to scores on a shortened version of the HVIC into an IND group (n = 25) and a COL group (n = 27). After correcting for outliers, no significant differences were found between the two groups regarding eye-movement patterns or memory. The two SA groups did, however, differ significantly from the American group but not the Chinese group in the original study by Chua et al. (2005). Discrepancies in IND-COL research in SA are likely due to a lack of comprehensiveness in terms of the cultural tasks included in the surveys. Increasing acculturation in post-Apartheid South Africa, especially among university students, may also play a large role. Further issues regarding IND-COL measurement in South Africa, as well as issues surrounding IND-COL measurement internationally were also discussed. Methodological issues in studying the links between IND-COL and cognition within a South African context were likely the reason behind the lack of differences found in this study in terms of eye-movement patterns and memory for the two SA groups.